Mineralogical characterization and thermodynamic modeling of synthesized ettringite from Ca-Al-SO4 suspensions. (1st February 2021) - Akula, Pavan; Little, Dallas N.
Highlights: Suspensions with five different stoichiometric ratios Ca(OH)2 to Al2 (SO4 )3 ·18H2 O (1:1, 3:1, 4:1, 5:1, and 6:1) are used in this study to evaluate ettringite. Thermodynamic models Gibb's Energy Minimization Selektor and Geochemist's workbench predicted ettringite as a stable phase for 3 out of 5 samples. The modeling results were experimentally verified with quantitative X-ray diffraction and thermogravimetric analysis. The results demonstrate the potential to predict ettringite formation using thermodynamic modeling. Abstract: Ettringite formation due to sulfate attack in Portland cement concrete (PCC) and chemically stabilized soils can cause volumetric instability and strength loss resulting in reduced performance life. Evaluating and possibly predicting ettringite formation is critical if structural integrity is to be preserved. Suspensions with five different stoichiometric ratios Ca(OH)2 to Al2 (SO4 )3 ·18H2 O (1:1, 3:1, 4:1, 5:1, and 6:1) are used in this study to evaluate ettringite formation both qualitatively and quantitatively. For all samples, Ca 2+ ions are supplied by Ca(OH)2 reagent; Al 3+ and SO 4 2 - ions are supplied by aqueous Al2 (SO4 )3 ·18H2 O. Thermodynamic modeling using a Gibb's energy minimization-based model (GEM-Selektor) is used for the quantitative evaluation of precipitated phases formed in the Ca-Al-SO4 suspension. In addition, a phase stability diagram is constructed with a law of mass action (LMA) based model (Geochemist's Workbench (GWB)). Mineralogical characterization of precipitated solid phases is performed using quantitative X-ray diffraction (QXRD), fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS). Characterization of the suspension is carried out using pH and electrical conductivity. Qualitatively, GEMS and GWB predicted ettringite as a stable phase for 3 out of 5 samples which is experimentally verified by QXRD and TGA. Quantitatively, the mean error in prediction using GEMS is approximately 4%. The results demonstrate the potential to predict ettringite formation using thermodynamic modeling.